The Cal Poly Product, 1962 (1962)
[00:00:02] A recording plays over talking about young minds and dreamers [00:00:19] A speaker tells the faculty that they have already taken the dare [00:01:06] Students from all over the world have traveled to Cal Poly's campus [00:01:18] 5,000 young minds will come to campus and come in contact with them looking for what they will supply [00:01:59] The speaker adds that some faculty have taught for years, and says you are never truly ready [00:02:27] They are here to refresh their understanding of why they are at Cal Poly [00:02:33] Another speaker talks about the hardships of being a faculty member [00:03:21] The first speaker highlights that they are all "old-timers," so it's not entirely new information [00:04:06] The second speaker then concludes that they wouldn't be anywhere else [00:04:23] Most people probably stick around due to the year round climate, beach, or mountains [00:04:37] People might sick around due to the activities: fishing or hunting [00:05:06] However, the first speaker underscores the real problem is finding a house to settle down in San Luis Obispo [00:05:36] The second speaker highlights that no one really understand Cal Poly until they've been there awhile [00:06:07] The faculty enjoys their field and they stay for the young people [00:06:17] It is presented that teachers want to teach, that's why they are teaching [00:06:30] Teaching at Cal Poly is different, the students are taught the Cal Poly way [00:07:35] The Cal Poly community are doers, showers, as well as fighters and scrapers for what they believe [00:07:50] The second speaker mentions that, that is why Cal Poly has grown so rapidly [00:07:59] Cal Poly is the largest undergraduate school for Agriculture and the second for Engineering [00:08:54] All the faculty comes together to fight hard for Cal Poly [00:09:07] The first speaker underlines that Cal Poly is more like a family, including students, faculty and staff [00:09:56] The second speaker talks about the importance of helping the students [00:10:07] Cal Poly is not old enough to accept mostly "legacies," since it is only 20 years old [00:10:39] The students, instructor relationship is the most important [00:10:58] Two, distinctive terms that are Cal Poly's successful philosophies are: Learn by Doing and The Upside Down Curriculum [00:12:54] The importance of student, instructor relationships is reiterated [00:12:57] The same kind of training that started the development of the Pomona campus [00:13:12] Cal Poly is the only regionally designate state college [00:13:40] The campus is outside city limits, but it produces 7 million dollars per year [00:13:57] It also has its own police and firefighter department with its own hospital [00:14:22] It also has its own transportation system with the largest car and bus pool for state colleges [00:14:57] El Mustang is a self supporting poly project that is both a public and printed newspaper created by students [00:15:55] The Cal Poly handbook and catalog are resources for the faculty [00:17:49] Cal poly is a college that has its "sleeves rolled up" [00:18:18] Organizations on campus will probably exceed eighty [00:18:58] The student activities office is set up to guide students [00:19:05] The college health center is also ready to help students [00:19:59] The counseling center is prepared to help students with any problems [00:21:45] The supplying of the facilities is also a challenge to accommodate due to Cal Poly know being a meeting place [00:23:19] The students, faculty, etc. are all apart of what makes Cal Poly's Product, which stems from the atmosphere on campus [00:23:37] Other distinguished victors have talked highly of Cal Poly while visiting [00:24:44] Singing concludes the talk